Human and non-human bodies that migrate: a review of studies of migrant objects (Polis (Santiago), 2025)
Generally, studies on transnational migrations have focused their attention on an anthropocentric and humanist perspective, without sufficiently considering the materiality on which migratory trajectories are also based. Therefore, this article develops, through a bibliographic review of studies, the lines of argument by which both epistemologically and methodologically the semiotic-material relationship in transnational mobilities is considered in research. In the findings, analyzes can be found in different contexts and countries that consider migrating objects or as elicitors of the experiences and lives of migrant subjects; or as enhancers of reaffirmations or new processes of individual and collective subjectification, and/or triggers of various forms of migrant memories.  However, there is less analytical development on the agency and potential that objects and artifacts themselves possess to promote, limit, authorize or enhance human mobilities.
Keywords: Objects, artifacts, memories, agency, migration; objects; artefacts; memories; agency; migration